A prospective report on the research developed at the Laboratory of Audio and Music Technology at USP - Faria, Regis Rossi A.; Thomasi, Ricardo; Monnazzi, João; Bonachela, Eduardo; Giolito, André; Lemos, Gabriel (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
This paper presents a concise report on the research developed at the Laboratory of Audio and Music Technology at the EACH-USP. The laboratory was founded in 2011 targeting the areas of music technology, musical acoustics and bioacoustics, strengthening its scope in 2019 to the areas of sound and music computing and audio engineering. Six projects are presented herein, describing their application areas, goals, achievements and perspectives.